HUMANISM IN ROBINSON CRUSOE BY DANIEL DEFOE = CHỦ NGHĨA NHÂN ĐẠO TRONG ROBINSON CRUSOE CỦA DANIEL DEFOE - Hoàng, Thị Hải Yến (2020)
This paper is a thumbnail of an adventurous man on an isolated land. Throughout the novel, this thesis aims to emphasize the humanism reflected by the author. The humanism is really described under the author’s talent writing. Furthermore, readers can have chance of investigating the period of Enlightenment. In addition, Daniel Defoe was the typical writer at this time because of novel “Robinson Crusoe”. First and foremost, chapter 1 gives a brief review on Literary theory which covers the conception and functions of Literature, the definition of Humanism and its characteristics. Notably, the four characteristics of Humanism are listed in part 3 which relate to Humanism in the novel and are analyzed in the graduation paper. Chapter 2 provides not only general background knowledge of the historical background and Daniel Defoe’s important events in his life but also the summary of the novel. The last and the main one, chapter 3 deals with some features of Humanism in the novel.